Spectrophotometric Determination of Lead(II) with 3-Hydroxy-3-m-Tolyl-1-o-Chlorophenyltriazene - Maroo, Usha; Sharma, Kavita; Maroo, Pradeep; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
3-Hydroxy-3-m-tolyl-1-o-chlorophenyltriazene has been used for the spectrophotometric determination of Pb(II). The reagent forms yellow lead complex composition 1 : 2 (Pb : R) between pH 6.9–7.3. Absorbance measurements were made at 404 nm. Values of molar absorptivity, Sandell's sensitivity, stability constant (log K) and free energy of formation were found to be 14,500 L mol–1 cm–1, 14.3 ng/cm2, 9.65 and 13.247 kcal/mol respectively. Beer's law is obeyed in the entire concentration range studied, i.e., 1.0 x 10–5 M to 6.0 x 10–5 M. It was possible to determine lead (8.28 mg) in presence of twofold molar excess of twenty cations and anions.